Microscopic Analysis of E-Cigarette Vapors Effects on the Eyes - Lolinia Agustina Florensia; Purnamawati Purnamawati; Erma Mexcorry Sumbayak (Jurnal MedScientiae, 2023)
Recently, e-cigarettes or VAPE have become a new trend among smokers. Known as a modern cigarette with a wide selection of flavors and aromas such as vanilla, raspberry and spearmint as well as abundant steam, making vaping a favorite activity among teenagers. This research is a literature study on various medical research journal databases such as PubMed, Science Direct, Cochrane and Google Scholar. Based on research results, it is known that the vapor from vaping causes dryness, thickening and even damage to the cornea. The occurrence of lipid peroxidation by free radicals contained in vaping vapor causes the eye protective layer "tear film" consisting of lipid, aqueous, and mucin layers to be damaged. Dry eye syndrome and damage to the eye epithelium are characterized by a decrease in the number of goblet cells and inflammation of the corneal tissue, even an increased of potential for cataracts can occur either by direct exposure or by inhalation of vapors which causes a systemic increase in oxidant levels.